2009
DOI: 10.1086/596488
|View full text |Cite
|
Sign up to set email alerts
|

Hospital‐Based Surveillance of Invasive Pneumococcal Disease among Young Children in Urban Nepal

Abstract: More than 60% of children aged <5 years who were admitted with fever and/or suspected invasive bacterial disease in urban Nepal had the clinical syndromes of meningitis and/or pneumonia. A new generation of pneumococcal vaccines that prevent infection with a broader range of serotypes may be necessary to most effectively control pneumococcal disease in young children in Kathmandu.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 13 publications
3
35
0
1
Order By: Relevance
“…Since April 2005, as part of a microbiological surveillance study, all children admitted to the children's ward of Patan Hospital with suspected invasive bacterial disease or pneumonia have routinely had blood samples and, where appropriate, cerebrospinal fluid (CSF) samples cultured. All pathogens isolated from blood and/or CSF samples were stored at Ϫ70°C (12,38). Hib disease-causing isolates were obtained from this collection for comparison with isolates from children carrying Hib.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since April 2005, as part of a microbiological surveillance study, all children admitted to the children's ward of Patan Hospital with suspected invasive bacterial disease or pneumonia have routinely had blood samples and, where appropriate, cerebrospinal fluid (CSF) samples cultured. All pathogens isolated from blood and/or CSF samples were stored at Ϫ70°C (12,38). Hib disease-causing isolates were obtained from this collection for comparison with isolates from children carrying Hib.…”
Section: Methodsmentioning
confidence: 99%
“…However, the absolute number of cases in the study was small, and there is still uncertainty about the relative importance of Hib in Asia. In urban Nepal, we have previously identified a significant burden of pneumonia in children less than 5 years old admitted to a hospital (12,38). While Hib is likely to be the cause of many of these cases of pneumonia, most children with Hib pneumonia have negative blood cultures, and confirmation is therefore not possible (6).…”
mentioning
confidence: 99%
“…Elerie J. Williams et al also could recover only 9 bacteria from culture of 199 CSF sample. (9) The positivity of CSF cultures in TBM has been reported to vary from 8% to 58% by several workers in India. (10) Our patients showed significant CSF leucocytosis with neutrophilic predominance (90%) and high CSF protein (>50 mg/dl) (72.7%) in bacterial meningitis compared to the nonbacterial meningitis group.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in its efforts to measure the burden of IPD around the world, the PneumoADIP programme 14 found that, while many sentinel systems with large populations in their catchment areas identified more than 30 hospitalized, laboratory-confirmed cases a year in children aged under 5 years, 7,15,16 others identified substantially fewer. 7,[17][18][19][20] However, the alternative approach of establishing sentinel surveillance at hospitals that treat a large proportion of their areas' IPD cases has the disadvantage that, without a population-based surveillance system, it is difficult to estimate the percentage of cases in the population seen at an individual hospital. Pooling several individual hospitals to create a sentinel system with a large enough total number of baseline cases may be more practical.…”
Section: Researchmentioning
confidence: 99%